New species of Latreillopsis Henderson, 1888 (Brachyura: Homolidae) and Neopalicus Moosa & Serène, 1981 (Brachyura: Palicidae) from the Hawaiian Islands - Castro, Peter; Naruse, Tohru (Zootaxa, 2014)
Two new species of brachyuran crabs belonging to Latreillopsis Henderson, 1888 (Homolidae) and Neopalicus Moosa & Serène, 1981 (Palicidae) respectively are described from Maui, Hawai‘i. The new species of Latreillopsis is distinguished from its nine congeners by a granular carapace and pereopods, a triangular G1, and by the distinctive ornamentation of its carapace and third maxillipeds; the new species of Neopalicus from its three congeners by the presence of three triangular anterolateral teeth, absence of extensions on the outer margins of the P3 and P4 propodi, dentate inner margins of the P3, P4 dactyli, and absence of ridges on the female abdomen. Also listed is Latreillia metanesa Williams, 1982 (Latreilliidae), recorded for the first time from the archipelago since its description from Albatross material collected in 1902.